Exogenous zinc mitigates salinity stress by stimulating proline metabolism in proso millet (Panicum miliaceum L.) - Mushtaq, Naveed Ul; Alghamdi, Khalid M.; Saleem, Seerat; Tahir, Inayatullah; Bahieldin, Ahmad; Henrissat, Bernard; Alghamdi, Mohammed Khalid; Rehman, Reiaz Ul; Hakeem, Khalid Rehman (Frontiers in Plant Science, 2023)
Salinity is one of the most concerning ecological restrictions influencing plant growth, which poses a devastating threat to global agriculture. Surplus quantities of ROS generated under stress conditions have negative effects on plants' growth and survival by damaging cellular components, including nucleic acids, lipids, proteins and carbohydrates. However, low levels of ROS are also necessary because of their role as signalling molecules in various development-related pathways. Plants possess sophisticated antioxidant systems for scavenging as well as regulating ROS levels to protect cells from damage. Proline is one such crucial non-enzymatic osmolyte of antioxidant machinery that functions in the reduction of stress. In the present study Zinc (Zn) was applied to elucidate its effect on proline metabolism and stress-responsive mechanisms in proso millet. The results of our study indicate the negative impact on growth and development with increasing treatments of NaCl. However, the low doses of exogenous Zn proved beneficial in mitigating the effects of NaCl by improving morphological and biochemical features. In salt-treated plants, the low doses of Zn (1 mg/L, 2 mg/L) rescued the negative impact of salt (150mM) as evidenced by increase in shoot length (SL) by 7.26% and 25.5% , root length (RL) by 21.84% and 39.07% and membrane stability index (MSI) by 132.57% and 151.58% respectively.The proline content improved at all concentrations with maximum increase of 66.65% at 2 mg/L Zn. Similarly, the low doses of Zn also rescued the salt induced stress at 200mM NaCl. The enzymes related to proline biosynthesis were also improved at lower doses of Zn. In salt treated plants (150mM), Zn (1 mg/L, 2 mg/L) increased the activity of P5CS by 19.344% and 21%. The P5CR and OAT activities were also improved with maximum increase of 21.66% and 21.84% at 2 mg/L Zn respectively. Similarly, the low doses of Zn also increased the activities of P5CS, P5CR and OAT at 200mM NaCl. Whereas P5CDH enzyme activity showed a decrease of 82.5% at 2mg/L Zn+150mM NaCl and 56.7% at 2mg/L Zn+200 mM NaCl. These results strongly imply the modulatory role of Zn in maintaining of proline pool during NaCl stress.